2005
DOI: 10.1098/rsif.2004.0019
|View full text |Cite
|
Sign up to set email alerts
|

Human foetal osteoblastic cell response to polymer-demixed nanotopographic interfaces

Abstract: Nanoscale cell-substratum interactions are of significant interest in various biomedical applications. We investigated human foetal osteoblastic cell response to randomly distributed nanoisland topography with varying heights (11, 38 and 85 nm) produced by a polystyrene (PS)/polybromostyrene polymer-demixing technique. Cells displayed islandconforming lamellipodia spreading, and filopodia projections appeared to play a role in sensing the nanotopography. Cells cultured on 11 nm high islands displayed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(172 citation statements)
references
References 52 publications
6
166
0
Order By: Relevance
“…The role of filopodia in sensing nanoscale topography was recently demonstrated on the 11 nm high islands. 38,39 Our results provide additional evidence of this phenomenon. For cells with a surface roughness of 13 nm on surfaces treated with 10.0 M NaOH, SEM images revealed that cells had more filopodia after a short time of culture ( Figure 6A-C).…”
Section: Discussionsupporting
confidence: 68%
“…The role of filopodia in sensing nanoscale topography was recently demonstrated on the 11 nm high islands. 38,39 Our results provide additional evidence of this phenomenon. For cells with a surface roughness of 13 nm on surfaces treated with 10.0 M NaOH, SEM images revealed that cells had more filopodia after a short time of culture ( Figure 6A-C).…”
Section: Discussionsupporting
confidence: 68%
“…According to recent studies, [19][20][21] cell adhesions are significantly affected by surface chemical composition and nanotopography. More specifically, the cell adhesion could be increased or decreased depending on the material and geometry used to construct the surface structure.…”
Section: Adhesions Of Mcf10a and Mcf7 Cellsmentioning
confidence: 99%
“…[12][13][14][15] It is noted in this regard that the cell adhesion is also modified on a nanostructured surface without specific proteins; it could be increased or decreased depending on the material and geometry used to construct the surface structure. [19][20][21] Recently, extensive efforts have been made to understand/control cell adhesions on various surface nanostructures using conventional or unconventional lithographic techniques. [22][23][24][25] A microfluidic system is advantageous for analysis of cell adhesion in various aspects because of small sample consumption, use of multiple parameters, and generation of large shear stress.…”
Section: Introductionmentioning
confidence: 99%
“…[53][54][55] The cellular response to the surface nanotopography and its correlation to the surface-bound proteins have been highlighted by Lim et al who showed that cell adhesion was unaffected by surface nanotopography if performed in the absence of serum. [56] This was a very important finding which allowed speculations that implant surfaces should be designed not for cells but more prominently for proteins as primary targets.…”
Section: Protein Adsorption Guided By Surface Physicochemical Factorsmentioning
confidence: 99%